PERLINDUNGAN HUKUM PEKERJA PEREMPUAN DALAM UU NO.13 TAHUN 2003 PERSPEKTIF SIYASAH SYAR'IYYAH: PERLINDUNGAN HUKUM PEKERJA PEREMPUAN UU NO. 13 - Arafa, Nur Arafa P. Tadda (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
The purpose of this study was to determine the from legal protection For women workers in law Number 13 of 2003 from the perspective of Siyasah Syar’iyyah, and to find out the implementation of legal protection for women workers in Law Number 13 of 2003 perspective Siyash Syar’iyyah. the main problem in this research is the legal Protection of womwn workers in Law Number 13 of 2003 prom the perspective Siyasah Syar’iyyah, and how the implementation of legal protection for women workers in Law Number 13 of 2003 from the perspective of Siyasa Syar’iyyah. This type of research is library research, which is a type of research centered on document studies. The result showed that the from of protection for women workers in Law Number 13 of 2003 covers menstrual protection, maternity dan maternity leave, protection of the right to breastfeeding opportunities, protection of the right not to be dismissed due to marriage, pregnancy and breasfeeding, and night work protection. Protection of women workers is carried out by the government, employers and workers. In the view of Siyasah Syariyyah, women are given protection from two sides, namely from the side of humanity and social rights, which also includes the protection specified in the applicable laws and regulations. Keywords: Legal protection; Woman: female Worker